A document of Ibadi jurisprudence related to the architecture of mosques / Benkari Naima - Naima, Benkari (Faculty of Architecture, Planning and Surveying, 2015)
The Ibâdi knowledgeable literature is still unknown in spite the numerous researches interested in this community and its historical, social, religious and even architectural productions. The present research comes in the continuity of the pioneering works of Joseph Schacht (Schacht, 1954), and Pierre Cuperly (Cuperly, 1988) about Ibâdism. It aims at casting light on the Ibâdi literature that represents a real source of information for the study of Ibâdism in the past and the present alike. This article analyses an Ibâdi manuscript from the 12th century, written by the scholar Abul’Abbas Ahmad. This document was the primary reference for the most important sources of Ibâdi legislation still in use by the community in its three main centers: M'zab, Djerba and Oman. The study of this document, along with other Ibâdi scholar literature that addressed some essential questions about mosques' design and construction, showed that this jurisprudence regulated in details the construction and management of mosques due to their importance for the formation and organization of the community.